Clinical characteristics of severe acute respiratory syndrome coronavirus 2 reactivation. Issue 5 (May 2020) - Ye, Guangming; Pan, Zhenyu; Pan, Yunbao; Deng, Qiaoling; Chen, Liangjun; Li, Jin; Li, Yirong; Wang, Xinghuan
Highlights: All reactivated patients presented normal aminotransferase levels. Throat swab samples from the reactivated patients indicated all positive for the virus. There might be no specific clinical characteristics to distinguish the reactivation of SARS-CoV-2. Summary: Objectives: Previous studies on the pneumonia outbreak caused by the 2019 novel coronavirus disease (COVID-19) were based on information from the general population. However, limited data was available for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) reactivation. This study aimed to evaluate the clinical characteristics of the SARS-CoV-2 reactivation. Methods: Clinical records, laboratory results, and chest CT scans were retrospectively reviewed for 55 patients with laboratory-confirmed COVID-19 pneumonia (i.e., with throat swab samples that were positive for SARS-CoV-2) who were admitted to Zhongnan Hospital of Wuhan University, Wuhan, China, from Jan. 8 to Feb. 10, 2020. Results: All 55 patients had a history of epidemiological exposure to COVID-19, and 5 (9%) patients who discharged from hospital presented with SARS-CoV-2 reactivation. Among the 5 reactivated patients, other symptoms were also observed, including fever, cough, sore throat, and fatigue. One of the 5 patients had progressive lymphopenia (from 1.3 to 0.56 × 10 9 cells per L) and progressive neutrophilia (from 4.5 to 18.28 × 10 9 cells per L). All 5 reactivated patients presented normal aminotransferase levels. Throat swab samples from the 5 reactivated patients were tested for SARS-CoV-2, indicating all positive for the virus. Conclusions: Findings from this small group of cases suggested that there was currently evidence for reactivation of SARS-CoV-2 and there might be no specific clinical characteristics to distinguish them.